Trade and development implications of financial services (UN New YorkUS, 2007)
Focuses on the global financial services (FS) market and emerging trends; the importance of FS for economic development, including universal access; the significance and elements of an effected regulatory and institutional framework, development issues arising from FS liberalization including the General Agreement on Trade in Services (GATS) and regional negotiations; and areas of potential export interest for developing countries.
Keywords: FINANCIAL SERVICES